Association of the BsmI, ApaI, TaqI, Tru9I and FokI Polymorphisms of the Vitamin D Receptor Gene with Nephrolithiasis in the Turkish Population - Cakir, Omer Onur; Yilmaz, Akin; Demir, Emre; Incekara, Kutluhan; Kose, Mustafa Omur; Ersoy Tunali, Nagehan (Urology Journal, 2016)
Purpose: To analyze the relationship between nephrolithiasis and vitamin D receptor (VDR) gene BsmI (rs1544410), ApaI (rs7975232), TaqI (rs731236), Tru9I (rs757343) and FokI (rs2228570) polymorphisms in a study group from the Turkish population. Materials and Methods: Ninety-eight patients with calcium oxalate kidney stones and 70 controls were enrolled in this study. Five polymorphisms of the VDR gene were studied using the Polymerase Chain Reaction Restriction Fragment Length Polymorphism (PCR-RFLP) method. Results: For all polymorphisms, genotype frequencies were in line with Hardy-Weinberg equilibrium in the patients and controls. For the BsmI polymorphism, allele frequency distribution was found to differ significantly between the patients and the controls (P < .05). The "B" allele was found to increase the risk of nephrolithiasis by approximately 1.5-fold (odds ratio = 1.55, 95% confidence interval: 1.00-2.40; P = .048). However, we did not find any statistically significant differences in the allele and genotype frequencies for the ApaI, TaqI, Tru9I and FokI polymorphisms. Proportionally, the "BAt" and "baT" haplotypes were more common than other haplotypes in the cases and controls, respectively. For the haplotypes of the BsmI and TaqI polymorphisms, the "bT" haplotype frequency was found to be common in both the patients and the controls. However, we did not find statistically significant differences between the cases and the controls for either the BsmI / ApaI / TaqI or the BsmI/TaqI haplotypes. Moreover, no relationship was identified between family history and development of stone disease. Conclusion: The "B" allele of the BsmI polymorphism of the VDR gene may increase stone development risk. Further investigations are needed to improve our knowledge regarding the genetic factors affecting urinary stone development.